2020
DOI: 10.1042/cs20201493
|View full text |Cite
|
Sign up to set email alerts
|

ACE2, a multifunctional protein – from cardiovascular regulation to COVID-19

Abstract: This Editorial, written by Guest Editors Professor Michael Bader, Professor Anthony J. Turner and Dr Natalia Alenina, proudly introduces the Clinical Science-themed collection on angiotensin-converting enzyme 2 (ACE2), a multifunctional protein – from cardiovascular regulation to coronavirus disease 2019 (COVID-19).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…This transmembrane glycoprotein is widely expressed in the respiratory system but has also been detected in cardiomyocytes, endothelial cells, vascular smooth muscle cells and cardiac fibroblasts [ 36 ]. ACE2 is a monocarboxypeptidase whose catalytic site promotes the conversion of angiotensin II (Ang II), a prohypertensive and profibrotic peptide, into angiotensin (1-7) (Ang (1-7)), a vasodilatory and cardioprotective agent [ 37 ]. It, therefore, plays a pivotal role in the regulation of the RAAS [ 38 ].…”
Section: Ace2 Biology and Physiological Functionsmentioning
confidence: 99%
“…This transmembrane glycoprotein is widely expressed in the respiratory system but has also been detected in cardiomyocytes, endothelial cells, vascular smooth muscle cells and cardiac fibroblasts [ 36 ]. ACE2 is a monocarboxypeptidase whose catalytic site promotes the conversion of angiotensin II (Ang II), a prohypertensive and profibrotic peptide, into angiotensin (1-7) (Ang (1-7)), a vasodilatory and cardioprotective agent [ 37 ]. It, therefore, plays a pivotal role in the regulation of the RAAS [ 38 ].…”
Section: Ace2 Biology and Physiological Functionsmentioning
confidence: 99%
“…On the one hand, ACE2 transforms Ang II to Ang 1-7 with an anti-inflammatory nature. On the other hand, ACE2 is a binding receptor and entry route for SARS-CoV-2 [6,8,9]. Since the findings of experimental studies indicated that ACEI/ARB increased cellular membrane-bound ACE2 (mACE2) expression, opinions have emerged about whether ACEI/ARB may heighten susceptibility to SARS-CoV-2 infection and worsen its prognosis; thus, the justification of renin-angiotensin system (RAS) inhibition in COVID-19 patients was addressed [10].…”
Section: Sars-cov-2 Ang II Ang 1-7 Interactionmentioning
confidence: 99%
“…In children or adolescent cohorts, where existence of confusing factors (i.e., epigenetic alterations) is lower, boys but not girls showed association of rs2158083, rs233575 and rs2074192 with hypertension ( 12 , 13 ). Nowadays, regulation of the ACE2 expression and activity has become essential for Coronavirus disease (COVID)-19 subjects, particularly for those with cardiovascular complications ( 6 , 14 ). Thus, further studies analyzing ACE2- SNPs and related haplotypes in young populations, could suggest predictive markers for CV diseases and molecular targets for CV therapy.…”
Section: Introductionmentioning
confidence: 99%